OPTIMIZATION OF MULTI-TRIP VEHICLE ROUTING PROBLEM WITH TIME WINDOWS USING GENETIC ALGORITHM - Yusuf Priyo Anggodo; Amalia Kartika Ariyani; Muhammad Khaerul Ardi; Wayan Firdaus Mahmudy (Journal of Environmental Engineering and Sustainable Technology, 2016)
This research studied the application of multitrip vehicle routing problem with time windows (VRPTW) on the problems of the tourist routes in Banyuwangi. The problems of ordinary VRPTW has only one route to the finish line that will be targeted with specific time limits while the multi-trip VRPTW has several tourist routes and one central point as the reference point for determining the route of the tour as well as the deadline for each tour. Genetic algorithm used to solve this problem because it can overcome the problem of combinatorial effectively and efficiently, moreover it can reach solutions globally so that it can produce the optimum solution. Chromosome on the Genetic Algorithm represents the permutation of the overall tour. After decoding there are three chromosome segments created, where each segment represents a visit of tourist attractions in one day. This research provides the optimal result i.e. a solution route with the shortest commute time and a fast computing time so it is very helpful in determining the route of the tourist trips with the closest mileage based on their places to stay (centre point).